THE “COMMUNITY POLICING” MODEL AS A TOOL FOR PARTNERSHIP BETWEEN THE POLICE AND THE COMMUNITY IN UKRAINE - Hulchuk, Yelyzaveta; Panova, Oksana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to analyse the peculiarities of implementing the “Community Policing” model in the activities of the National Police of Ukraine, to define its main principles, objectives, and prospects for development in the context of law enforcement reform. The article examines the relationship between the police and local communities and the impact of partnership interaction on the level of public trust and community safety. Research methods: systemic, comparative-legal, and analytical approaches were used. The study analyses the international experience of implementing the “Community Policing” concept in the United Kingdom, the United States, Poland, and Canada. A review of national legal acts, scholarly research, and practical initiatives of the Ministry of Internal Affairs of Ukraine and international organisations (UNDP, EUAM, ICITAP) was conducted, aimed at developing community officers and building a safe environment. Results: it has been substantiated that the “Community Policing” model in the Ukrainian context is an important element of democratic governance in the field of security. Its effectiveness depends on proper legal regulation, adequate funding, professional training of personnel, and public trust. It is noted that successful pilot projects demonstrate the possibility of integrating international standards into the activities of the National Police. At the same time, the need for further improvement of the legal framework, expansion of community partnerships, and the introduction of mechanisms for assessing the effectiveness of the concept’s implementation is emphasised. Discussion: the “Community Policing” model involves a shift in the approach to performing police functions — from punitive to preventive, from distant control to open cooperation. Its implementation contributes to building trust, increasing transparency in police actions, and enhancing citizens’ involvement in security matters. The introduction of this model in Ukraine is of a complex nature and requires coordinated efforts by the state, the police, and local self-government.